?EFFECTS OF NaCI AND CaCl2 ON CALLUS TISSUE OF GOSSYPIUM HIRSUTUM L.CV. ACALA SJ2 (Biological Sciences - PJSIR, 1999)
The interactive effect of NaC1 and CaCI2 on the leaf and petiole-derived calli of Acala SJ2 (Gossypium hirsutum. L.)grown on Murashige and Skoog (1962) tissue culture medium was studied. Relative growth rate was used to assess the tolerance. NaCI reduced growth rate while calcium partially ameliorated the effects of NaCI. Water content of the callus decreased significantly with increasing salinity levels in the culture medium while reverse was true at high calcium level. NaCI resulted in higher Na' and lower K+and Mg+2.The reverse was true for calcium up to 30 mol m'. C+2concentration decreased with increasing salinity but increased at higher calcium levels. Cl contents increased with increasing salinity and calcium levels in the medium. NO'3' SO/ and P04') were unaffected by salinity. In both kinds of callus, the highest calcium (up to 60 mol m') and salinity (200 mol m") levels increased proline accumulation. The correlation between relative growth rate and proline concentration was -0.98 (leaf callus) and - 0.97 (petiole callus). The results suggested that salinity reduced the callus growth while calcium ameliorated its toxic effects. Proline acted as a compatible solute. The callus cultures from different explant sources of the same genotype behaved differently in vitro.